High resolution computed tomography of the lung in lifelong non-smoking patients with rheumatoid arthritis. Issue 4 (April 1995) - Hassan, W U; Keaney, N P; Holland, C D; Kelly, C A
Abstract : OBJECTIVES–To define pulmonary involvement on high resolution computed tomography (HRCT) of the thorax in lifelong non-smoking rheumatoid arthritis patients and to relate the results to pulmonary function, bronchial reactivity, and a variety of clinical and serological factors. METHODS–Twenty lifelong non-smoking RA patients (mean age 59 years (range 44-72; 18 females) were studied. Detailed medical and drug histories were taken. Protease inhibitor phenotype (Pi) and HLA-DR4 status were assessed. Schirmer's tear tests were performed to detect keratoconjunctivitis sicca (KCS). Spirometry, flow volume loops, and gas transfer factor measurement were recorded. The degree of bronchial reactivity (PC20 FEV1) was measured by a methacholine inhalation test. Chest and hand radiographs and HRCT of the lung were performed in all patients. RESULTS–Thirteen patients were HLA-DR4 positive. Eighteen had the Pi MM and two the Pi MS phenotype. Eight patients had evidence of KCS on Schirmer's tear testing. Ten patients achieved PC20 FEV1 in the methacholine inhalation test. All the patients had normal chest radiographs and all showed evidence of erosive arthropathy on hand radiographs. Five patients (25%) showed basal bronchiectasis and one mild interstitial lung disease on HRCT. All five patients with bronchiectasis had the Pi MM phenotype, four had HLA-DR4, four had KCS and three achieved PC20 FEV1; these values were not significantly different (p > 0.05) from those in patients without bronchiectasis. CONCLUSION–Using the highly sensitive technique of HRCT, we found evidence to suggest that the incidence of bronchiectasis in lifelong non-smoking RA patients may be much higher than previously reported.